Introduction to Planetary Science The Geological Perspective - Faure, Gunter; Mensing, Teresa M.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
This textbook is intended to be used in a lecture course for college students majoring in the Earth Sciences. Planetary Science provides an opportunity for these students to apply a wide range of subject matter pertaining to the Earth to the study of other planets of the solar system and their principal satellites. As a result, students gain a wider perspective of the different worlds that are accessible to us and they are led to recognize the Earth as the only oasis in space where we can live without life-support systems. The subject matter is presented in 24 chapters that lead the reader through the solar system starting with historical perspectives on space exploration and the development of the scientific method. The presentations concerning the planets and their satellites emphasize that their origin and subsequent evolution can be explained by applications of certain basic principles of physics, chemistry, and celestial mechanics and that the surface features of the solid bodies in the solar system can be interpreted by means of the principles of geology. Organized in a hierarchical manner so that every chapter builds on preceding ones Abundantly illustrated with diagrams and color images Includes problem sets and a glossary
The Urge to Explore -- From Speculation to Understanding -- The Planets of the Solar System -- Life and Death of Stars -- Origin of the Solar System -- Earth: Model of Planetary Evolution -- The Clockwork of the Solar System -- Meteorites and Impact Craters -- The Earth-Moon System -- Mercury: Too Hot for Comfort -- Venus; Planetary Evolution Gone Bad -- Mars: The Little Planet that Could -- Asteroids: Shattered Worlds -- Jupiter: Heavy-Weight Champion -- Galilean Satellites: Jewels of the Solar System -- Saturn: The Beauty of Rings -- Titan: An Ancient World in Deep Freeze -- Uranus: What Happened Here? -- Neptune: More Surprises -- Pluto and Charon: The Odd Couple -- Ice Worlds at the Outer Limit -- Comets: Coming Inside from the Cold -- Earth: The Cradle of Humans -- Brown-Dwarf Stars and Extrasolar Planets.
Keywords: GEOCHEMISTRY; PHYSICAL GEOGRAPHY; MINERALOGY; PLANETOLOGY; ASTROPHYSICS; GEOSCIENCES; PLANETOLOGY; GEOCHEMISTRY; GEOPHYSICS/GEODESY.; MINERALOGY; ASTROPHYSICS